dy(xy-3x+6y-18)-dx(xy+4x-y-4)=0

Simple and best practice solution for dy(xy-3x+6y-18)-dx(xy+4x-y-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for dy(xy-3x+6y-18)-dx(xy+4x-y-4)=0 equation:


Simplifying
dy(xy + -3x + 6y + -18) + -1dx(xy + 4x + -1y + -4) = 0

Reorder the terms:
dy(-18 + -3x + xy + 6y) + -1dx(xy + 4x + -1y + -4) = 0
(-18 * dy + -3x * dy + xy * dy + 6y * dy) + -1dx(xy + 4x + -1y + -4) = 0

Reorder the terms:
(-3dxy + dxy2 + -18dy + 6dy2) + -1dx(xy + 4x + -1y + -4) = 0
(-3dxy + dxy2 + -18dy + 6dy2) + -1dx(xy + 4x + -1y + -4) = 0

Reorder the terms:
-3dxy + dxy2 + -18dy + 6dy2 + -1dx(-4 + 4x + xy + -1y) = 0
-3dxy + dxy2 + -18dy + 6dy2 + (-4 * -1dx + 4x * -1dx + xy * -1dx + -1y * -1dx) = 0

Reorder the terms:
-3dxy + dxy2 + -18dy + 6dy2 + (4dx + 1dxy + -4dx2 + -1dx2y) = 0
-3dxy + dxy2 + -18dy + 6dy2 + (4dx + 1dxy + -4dx2 + -1dx2y) = 0

Reorder the terms:
4dx + -3dxy + 1dxy + dxy2 + -4dx2 + -1dx2y + -18dy + 6dy2 = 0

Combine like terms: -3dxy + 1dxy = -2dxy
4dx + -2dxy + dxy2 + -4dx2 + -1dx2y + -18dy + 6dy2 = 0

Solving
4dx + -2dxy + dxy2 + -4dx2 + -1dx2y + -18dy + 6dy2 = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'd'.
d(4x + -2xy + xy2 + -4x2 + -1x2y + -18y + 6y2) = 0

Subproblem 1

Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0

Subproblem 2

Set the factor '(4x + -2xy + xy2 + -4x2 + -1x2y + -18y + 6y2)' equal to zero and attempt to solve: Simplifying 4x + -2xy + xy2 + -4x2 + -1x2y + -18y + 6y2 = 0 Solving 4x + -2xy + xy2 + -4x2 + -1x2y + -18y + 6y2 = 0 Move all terms containing d to the left, all other terms to the right. Add '-4x' to each side of the equation. 4x + -2xy + xy2 + -4x2 + -1x2y + -18y + -4x + 6y2 = 0 + -4x Reorder the terms: 4x + -4x + -2xy + xy2 + -4x2 + -1x2y + -18y + 6y2 = 0 + -4x Combine like terms: 4x + -4x = 0 0 + -2xy + xy2 + -4x2 + -1x2y + -18y + 6y2 = 0 + -4x -2xy + xy2 + -4x2 + -1x2y + -18y + 6y2 = 0 + -4x Remove the zero: -2xy + xy2 + -4x2 + -1x2y + -18y + 6y2 = -4x Add '2xy' to each side of the equation. -2xy + xy2 + -4x2 + -1x2y + -18y + 2xy + 6y2 = -4x + 2xy Reorder the terms: -2xy + 2xy + xy2 + -4x2 + -1x2y + -18y + 6y2 = -4x + 2xy Combine like terms: -2xy + 2xy = 0 0 + xy2 + -4x2 + -1x2y + -18y + 6y2 = -4x + 2xy xy2 + -4x2 + -1x2y + -18y + 6y2 = -4x + 2xy Add '-1xy2' to each side of the equation. xy2 + -4x2 + -1x2y + -18y + -1xy2 + 6y2 = -4x + 2xy + -1xy2 Reorder the terms: xy2 + -1xy2 + -4x2 + -1x2y + -18y + 6y2 = -4x + 2xy + -1xy2 Combine like terms: xy2 + -1xy2 = 0 0 + -4x2 + -1x2y + -18y + 6y2 = -4x + 2xy + -1xy2 -4x2 + -1x2y + -18y + 6y2 = -4x + 2xy + -1xy2 Add '4x2' to each side of the equation. -4x2 + -1x2y + -18y + 4x2 + 6y2 = -4x + 2xy + -1xy2 + 4x2 Reorder the terms: -4x2 + 4x2 + -1x2y + -18y + 6y2 = -4x + 2xy + -1xy2 + 4x2 Combine like terms: -4x2 + 4x2 = 0 0 + -1x2y + -18y + 6y2 = -4x + 2xy + -1xy2 + 4x2 -1x2y + -18y + 6y2 = -4x + 2xy + -1xy2 + 4x2 Add 'x2y' to each side of the equation. -1x2y + -18y + x2y + 6y2 = -4x + 2xy + -1xy2 + 4x2 + x2y Reorder the terms: -1x2y + x2y + -18y + 6y2 = -4x + 2xy + -1xy2 + 4x2 + x2y Combine like terms: -1x2y + x2y = 0 0 + -18y + 6y2 = -4x + 2xy + -1xy2 + 4x2 + x2y -18y + 6y2 = -4x + 2xy + -1xy2 + 4x2 + x2y Add '18y' to each side of the equation. -18y + 18y + 6y2 = -4x + 2xy + -1xy2 + 4x2 + x2y + 18y Combine like terms: -18y + 18y = 0 0 + 6y2 = -4x + 2xy + -1xy2 + 4x2 + x2y + 18y 6y2 = -4x + 2xy + -1xy2 + 4x2 + x2y + 18y Add '-6y2' to each side of the equation. 6y2 + -6y2 = -4x + 2xy + -1xy2 + 4x2 + x2y + 18y + -6y2 Combine like terms: 6y2 + -6y2 = 0 0 = -4x + 2xy + -1xy2 + 4x2 + x2y + 18y + -6y2 Simplifying 0 = -4x + 2xy + -1xy2 + 4x2 + x2y + 18y + -6y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

d = {0}

See similar equations:

| 72=24 | | 8/27+1/9+1/3(4/3)= | | 6y^2-31y+25=0 | | 11k^2+18k+25=0 | | 5+0.14285714285x=7 | | 8/27+1/9+1/3.4/3= | | 2x-1[4x(5)]= | | 0.3x+0.2(10)=0.1(x+20) | | 2y-5=5x+10 | | 4a+5b-9= | | 84-(4x+15)=4(x+6)+x | | -4m-6m=3m-4m+2 | | 13x^2y^2+22xy+1=0 | | 4x+6(x-6)=-126 | | h^2-7k=0 | | -5(4m+6)=-3(4m-2) | | 0.5t+8=1 | | 2x-4-3x+3=x-3 | | 4x^2+10x-6=186 | | -5x+3=-9x-39 | | 22x-7-12x+4=23x-4-13x+12 | | 15+4t=4(t+3) | | P^2-18p-29=7 | | ln(2)=x | | 7q+17=5q+33 | | -4+52x-48x^2=0 | | 6a^2+6=300 | | (-7)y=49 | | 5x=4x+22 | | 4.9t^2-20t+8=0 | | 9b+8b=13+8 | | -18=9+4(z-7) |

Equations solver categories